GERAKAN "DAKWAH" AGAMA KHONGHUCU DI KALIMANTAN BARAT - Nurhadijah, Elis (Jurnal Al-Hikmah: Jurnal Dakwah, 2023)
This article discusses the Confucian Religious Movement in West Kalimantan. The Confucian religion, which originated from China, has entered West Kalimantan along with the arrival of ethnic Chinese. This research uses qualitative research methods with a phenomenological perspective. Data was obtained from interviews with Confucian clergy and the High Council of Indonesian Confucian Religions (MATAKIN) chairman, West Kalimantan. Through the results of interviews, it was concluded that the Confucianism movement in West Kalimantan was a form of effort made by the Confucian clergy to strengthen the teachings of the Prophet Kongzi's life to his followers, especially after the New Order. One of the methods used by Confucian clergy is providing guidance, which takes the form of religious services and Sunday school. This coaching is usually carried out at the temple and also at a foundation. The challenge in the process of developing Confucian people is the awareness of these people. Confucian clergy will not force their congregation to follow invitations or invitations in the context of carrying out guidance. Therefore, the self-awareness of each congregation member is what Confucian clergy hope for. The development of the Confucian Religion in West Kalimantan is still good, as evidenced by the Indonesian Confucian Religious Council (MAKIN) in every district/city.Artikel ini membahas terkait Gerakan Agama Konghucu di Kalimantan Barat. Agama Konghucu yang berasal dari Tiongkok ini telah masuk ke Kalimantan Barat seiring dengan datangnya Etnis Tionghoa. Penelitian ini menggunakan metode penelitian kualitatif dengan sudut pandang fenomenologi. Data diperoleh dari hasil wawancara kepada rohaniwan Konghucu serta ketua Majelis Tinggi Agama Konghucu Indonesia (MATAKIN) Kalimantan Barat. Melalui hasil wawancara, diperoleh kesimpulan bahwa gerakan Agama Konghucu di Kalimantan Barat merupakan bentuk upaya yang dilakukan oleh rohaniwan Konghucu untuk menguatkan ajaran kehidupan Nabi Kongzi kepada umat-umatnya terkhusus pasca orde baru. Salah satu cara yang dilakukan oleh rohaniwan Konghucu ini adalah denagn melakukan pembinaan yang terwujud dalam bentuk kebaktian dan sekolah minggu. Pembinaan ini biasanya dilakukan di Klenteng dan juga pada sebuah yayasan. Adapun tantangan dalam proses pembinaan umat Konghucu adalah kesadaran dari umat tersebut. Rohaniwan Konghucu tidak akan memaksa umatnya untuk mengikuti ajakan atau undangan dalam rangka pelaksanaan pembinaa. Maka dari itu, kesadaran diri masing-masing dari umat yang diharapkan oleh para rohaniwan Konghucu. Perkembangan Agama Konghucu di Kalimantan Barat saat ini sudah bisa dikatakan lumayan baik, terbukti dengan adanya Majelis Agama Konghucu Inodnesia (MAKIN) disetiap kabupaten/kota.